Antimicrobial effect of farnesol, a Candida albicans quorum sensing molecule, on Paracoccidioides brasiliensis growth and morphogenesis - Silva-Pereira Ildinete; Kyaw Cynthia M; Báo Sônia N; Mello-; Braz Shélida V; De-; Derengowski Lorena S (BMC, 2009)
Abstract Background Farnesol is a sesquiterpene alcohol produced by many organisms, and also found in several essential oils. Its role as a quorum sensing molecule and as a virulence factor of Candida albicans has been well described. Studies revealed that farnesol affect the growth of a number of bacteria and fungi, pointing to a potential role as an antimicrobial agent. Methods Growth assays of Paracoccidioides brasiliensis cells incubated in the presence of different concentrations of farnesol were performed by measuring the optical density of the cultures. The viability of fungal cells was determined by MTT assay and by counting the colony forming units, after each farnesol treatment. The effects of farnesol on P. brasiliensis dimorphism were also evaluated by optical microscopy. The ultrastructural morphology of farnesol-treated P. brasiliensis yeast cells was evaluated by transmission and scanning electron microscopy. Results In this study, the effects of farnesol on Paracoccidioides brasiliensis growth and dimorphism were described. Concentrations of this isoprenoid ranging from 25 to 300 μM strongly inhibited P. brasiliensis growth. We have estimated that the MIC of farnesol for P. brasiliensis is 25 μM, while the MLC is around 30 μM. When employing levels which don't compromise cell viability (5 to 15 μM), it was shown that farnesol also affected the morphogenesis of this fungus. We observed about 60% of inhibition in hyphal development following P. brasiliensis yeast cells treatment with 15 μM of farnesol for 48 h. At these farnesol concentrations we also observed a significant hyphal shortening. Electron microscopy experiments showed that, despite of a remaining intact cell wall, P. brasiliensis cells treated with farnesol concentrations above 25 μM exhibited a fully cytoplasmic degeneration. Conclusion Our data indicate that farnesol acts as a potent antimicrobial agent against P. brasiliensis. The fungicide activity of farnesol against this pathogen is probably associated to cytoplasmic degeneration. In concentrations that do not affect fungal viability, farnesol retards the germ-tube formation of P. brasiliensis, suggesting that the morphogenesis of this fungal is controlled by environmental conditions.